Marriage and divorce among young adult cancer survivors - Kirchhoff, Anne C. (J Cancer Surviv, 2012)
PURPOSE: We examined marital outcomes among cancer survivors diagnosed during early adulthood from the 2009 Behavioral Risk Factor Surveillance System dataset. METHODS: Eligible participants were ages 20–39 years. Of the 74,433 eligible, N=1,198 self-reported a cancer diagnosis between the ages of 18 and 37, were ≥2 years past diagnosis, and did not have non-melanoma skin cancer. The remaining N=67,063 were controls. Using generalized linear models adjusted for age, gender, race, and education, we generated relative risks (RR) and 95 % confidence intervals (95 % CI) to examine survivor status on indicators of ever married, currently married, and divorced/separated. RESULTS: Survivors were slightly older than controls [33.0 (SD=3.8) vs. 30.0 (SD=4.0); p<0.001]. Average time since diagnosis was 7.4 years. Most common diagnoses were cervical (females; 45 %) and non-Hodgkin lymphoma (males; 20 %). Survivors were less likely to be currently married than controls (58 % vs. 64 %; RR=0.92, 95 % CI 0.85–0.99). Among ever married participants, survivors were at an increased risk of divorce/separation than controls (18 % vs. 10 %; RR=1.77, 95 % CI 1.43–2.19). Divorce/separation risk persisted for female survivors (RR 1.83, 95 % CI 1.49–2.25), survivors ages 20–29 (RR 2.57, 95 % CI 1.53–4.34), and survivors ages 30–39 (RR 1.62, 95 % CI 1.29–2.04). CONCLUSIONS: The emotional and financial burdens of cancer may lead to marital stress for younger cancer survivors. IMPLICATIONS FOR CANCER SURVIVORS: Young survivors may face a higher risk of divorce; support systems are needed to assist them in the years following diagnosis.